3 - Editorial - Abdallah S. Bujra, (CODESRIA Bulletin, 2025)
Editor’s Note: This was the inaugural Editorial Prof. Abdalla Bujra wrote for the ﬁrst issue of Africa Development, Vol. 1, no. 1, 1976. Africa Development has grown into a premier social science research journal that is currently in its 51st year of publication. The Article is available at https://doi.org/10.57054/ad.v1i1 This is the ﬁrst, and hopefully the only, editorial that will ap- pear in this journal. However, since this is the ﬁrst issue, a statement about the objectives of the journal and the sponsoring organization is both necessary and appropriate. Africa Development is a journal of the Council for the Development of Economic and Social Research in Africa (CODESRIA). The main purpose of the journal is to provide a forum for African (and non-African) scholars to critically analyse the problems emanating from the continuous process of underdevelopment, past and present, taking place in Africa. That underdevelopment of the African continent is a long-standing historical process that began even before the advent of formal colonialism, is now grudge ingly accepted even by conservative scholars. The so-called Africanists had, until recently, presented us with a simplistic and factually incorrect view of the African past as being suspended in a ‘traditional time- lessness’ where, since time immemorial, the varied social systems of African societies existed in a perfect, almost mechanical, harmony. At one point, European Africanists were arrogantly stating that African societies had no history (before colonization) because such societies did not possess a script with which to record events. (And in any case, since such societies were structurally harmonious and unchanging, i.e. not developing, there were no important events and process- es worth recording! So even if some societies had an alphabet, this would have been used mainly to record marriage ceremonies, and to draw up genealogies!) This extreme, unscientiﬁc view has now of course been abandoned. It has been replaced by a more sophisticated school which holds that each African society in fact had its particular and glorious history. This African history, however, consists of tribal migration, tribal warfare and the building up of political institutions, from kinship to kingship.